5-Fluorouracil Combined with Rutaecarpine Synergistically Suppresses the Growth of Colon Cancer Cells by Inhibiting STAT3 [Retraction] - Yu Z; Chan S; Wang X; Sun R; Wang M; Wang Z; Zuo X; Chen J; Zhang H; Chen W (Dove Medical Press, 2024)
Yu Z, Chan S, Wang X, et al. Drug Des Devel Ther. 2023;17:993–1006. At the authors request, the Editor and Publisher of the journal Drug Design, Development and Therapy have retracted the published article. Following publication of the article, the authors raised concerns about the duplication of images from Figure 4. Specifically, The images for Figure 4G, HCT116, RUT and 5-FU, have been duplicated. The authors wished to apologize for this error and no longer have confidence in the data and corresponding findings. To maintain academic standards, the authors requested to retract the article and the Editor and Publisher agreed with this decision. We have been informed in our decision-making by our editorial policies and COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.